Applications of vibrational spectroscopy in the study of flavin-based photoactive proteins. Issue 6 (2011) - Li, Jiang; Kitagawa, Teizo
Abstract : Flavin cofactor is known to perform diverse biological functions. Recently, its role as a photoreceptor has been identified. So far, three classes of photoactive flavoproteins have been recognized: phototropin with LOV (Light, Oxygen and Voltage) domain, blue light sensory protein with BLUF (Blue Light sensing Using Flavin adenine dinucleotide) domain and photolyase/cryptochrome protein with PHR (Photolyase Homology Region) domain. Photochemistry of flavin is the key to unravel the reaction mechanisms of photoactive flavoproteins in their biological functions such as DNA repair or signal transduction. Vibrational (Infrared and Raman) spectroscopy is a useful and sensitive tool to investigate the photochemistry of flavin in protein environments and has significantly contributed to elucidate the reaction mechanisms of these photoactive proteins. This study will survey recent advances in vibrational spectroscopic studies on this topic and remaining questions to be answered.